Innovative Power Generation System for Large Ships Based on Fuel Cells: A Technical–Economic Comparison with a Traditional System - Alessandro Ruvio; Stefano Elia; Manlio Pasquali; Roberto Pibiri; Stephen McPhail; Matteo Fontanella (Energies)
At present, shipping companies are aiming to meet better energy and environmental requirements when designing large cruise ships, thus decreasing emissions, increasing efficiency and reliability and greatly reducing maintenance time and costs. This paper provides a technical–economic comparison for a real case study, including a complete feasibility study regarding the sizing of a generation system to supply base hotel loads, between two power plant architectures focused on fuel cells and diesel generators for a cruise ship. The paper describes, in detail, an innovative solid oxide fuel cell (SOFC) generation system, which offers high efficiency and low emissions, assessed for its technical, economic and environmental performance. This study examines generators for hotels, requiring continuous service at constant load and a 1 MW power supply. The work relates to ships with a tonnage of more than 100,000 tons. Subsequently, considering that, in the case study, the diesel generators are powered by LNG (liquefied natural gas), there will also be a comparison with a case where both systems are simply powered by LNG. The main technical specifications required by shipbuilders for choosing the most suitable system for on-board generation (weight, volume, maintenance intervals and operations, as well as investment and operational expenses) are analyzed and described. The economic comparison is based on two extreme assumptions of the purchase and operating costs of the fuel cell system and returns a different result depending on the assumption adopted. The usefulness of the proposed solution based on fuel cells is demonstrated on the basis of an accurate technical, energetic and economic comparison with the conventional technologies based on diesel generators. The work is completed by evaluating the overall power-generating reliability improvement achievable with the new technology, in comparison with the traditional system. The comparison between the fuel cell system and the diesel system shows that the former has a higher weight (+40%), volume (+75%) and initial investment cost (3–6 times higher). However, the lower LNG consumption reduces the annual operating cost and the size and weight of the on-board tanks or, with the same tank capacity, increases the system’s range. The overall reliability of the fuel cell system is significantly higher than that of the traditional system.